Energy and carbon footprint analysis of municipal wastewater treatment process integrated with food waste disposer. (15th November 2022) - Guan, Jianyu; Zhuang, Huichuan; Lau, Chun Yin; Leng, Ling; Yeung, Chi Shun; Vuppaladadiyam, Arun Krishna; Wang, Huaimin; Tse, Ho-Yin; Leu, Shao-Yuan
Abstract: Household food waste (FW) management has become an emerging environmental issue affecting sustainable urban development. The application of in-sink domestic food waste disposers (FWDs) have brought significant public attentions due to its simplified waste handling process and reduced household expenses. However, the potentail negative impacts of mixing FW in the sewer system, i.e., the reduction of aeration efficiency in wastewater treatment processes (WWTPs) and corresponding increase of greenhouse gas (GHG) emission, has not been quantified. In this study, real-time oxygen transfer efficiency in processing water was measured in WWTPs receiving negligible amount of FW and compared with those receiving sewage combined with FWD effluent. WWTP receiving sewage with FW had 6–10% lower oxygen transfer rate than those without FW, resulting in extra energy consumptions of 0.25–0.30 kWh/m 3 and GHG emissions of 0.35–0.41 kg CO2 /m 3 . For estimating the substantial impacts of FWD to the carbon cycle, sludge treatment scenarios were designed among anaerobic digestion (AD), incineration, and direct landfill disposal. Compared with AD (−0.07 kWh/kg) and incineration (0.112 kWh/kg), FWD/WWTP consumed more energy (0.69–0.9 kWh/kg) and most of which (∼64%) was required by aeration. The operating costs of WWTPs also increased by 1.6–2.1 times in comparison with those did not receive FW. The application of FWD, however, could reduce the overall GHG emissions by 35.2% in comparison with direct landfilling. Decision-makers should guide householders and waste management practitioners through new policies such as carbon credits and/or waste charging scheme to support more environmental-friendly disposal methods of FW, especally when the maturity of socio-economic conditions are of concerns. Compared with AD and incineration, FWD may be a compromising alternative to control GHG emissions with existing wastewater treatment facilities especially to those regions where complete FW classification and treatment are not well-established. Graphical abstract: Image 1 Highlights: Carbon emission in wastewater treatment plants with food waste disposer was studied. Dynamic changes of oxygen transfer efficiency were monitored. Additional energy consumption from aeration was quantified by off-gas tests. Diffusor fouling cost in non-food sewage was calculated for the first-time. Energy/carbon balance for region-based food waste diversions was reported.